Significance of MEFV Gene R202Q Polymorphism in Turkish Familial Mediterranean Fever Patients - Yigit, S.; Karakuş, N.; Taşlıyurt, T.; Kaya, S.U.; Burul-Bozkurt, N.; Kisacik, B. (Elsevier Science BV, 2012)
Objective: FamiSeDl Mediterranean fever (FMF) is an autosomal recessive disorder characterized by recurrent attacks of fever and inflammation in the peritoneum, synovium, or pleura, accompanied by pain. The disease is associated with mutations in the Mediterranean fever (MEFV) gene, which encodes for the pyrin protein. The aim of this study was to explore the frequency and clinical significance of the R202Q (c.605G>A) polymorphism in exon 2 of the MEFV gene in a cohort of Turkish patients with FMF. Methods: The study included 191 patients with FMF and 150 healthy controls. Genomic DNA was isolated and genotyped using polymerase chain reaction (PCR)-based restriction fragment length polymorphism (RFLP) assay for the MEFV gene R202Qpolymorphism. Results: The genotype and allele frequencies of R202Q polymorphism showed a statistically significant difference between FMF patients and controls (p<. 0.0001 and p=0.0004, respectively) and especially the homozygous AA genotype was significantly higher in FMF patients than healthy controls (p=0.0002; odds ratio. =6.27; 95% CI. =2.1-18.3). However no significant association was observed between clinical and demographic features of FMF patients and R202Qpolymorphism. Conclusion: The results of this study showed that there was a high association between MEFV gene R202Q polymorphism and FMF. R202Q polymorphism should be included in routine molecular diagnosis of FMF patients. © 2012 Elsevier B.V.
Keywords: Familial Mediterranean Fever (FMF); MEFV Gene; R202Q